Sustainable growth of informal social microenterprises (ISMs) in a developing country: a multidimensional assessment - Khan, Eijaz Ahmed (Curtin University, 2014)
This study investigates the factors affecting the sustainable growth of informal social microenterprises (ISMs) in the context of a developing country. A mixed method approach was used. At first, a comprehensive model was developed through a literature review and field study analysis. Next, the data of the survey was analysed through Partial Least Square approach. Results indicate that various resources and capabilities affect the ISMs growth. This study proposes several future directions and policy implications.